On an international training of mathematically talented students: assets of the 20 years of the “Nagy Károly Mathematical Student-meetings” - Kántor, Sándor; Kántor, Tünde (Teaching Mathematics and Computer Science, 2012)
The focus of this paper is to present the gems of the "Nagy Károly Mathematical Student-meetings" in Rév-Komárom (Slovakia) from 1991 to 2010. During these 20 years there was done a lot of work to train mathematically talented students with Hungarian mother tongue and to develop their mathematical thinking, and to teach them problem solving and heuristic strategies for successful acting on the competitions. We collected the most interesting problems and methods presented by the trainer teachers.